Prototype and numerical studies of interference characteristics of two ski-jump jets from opening spillway gates. Issue 2 (20th April 2015) - Xiao, Yexiang; Wang, Zhengwei; Zeng, Jidi; Zheng, jintai; Lin, Jiayang; Zhang, Lanjin
Abstract : Purpose: – The purpose of this paper is to experimentally and numerically investigate the interference characteristics between two ski-jump jets on the flip bucket in a large dam spillway when two floodgates are running. Design/methodology/approach: – The volume of fluid (VOF) method together with the Realizable k-ε turbulence model were used to predict the flow in two ski-jump jets and the free surface motion in a large dam spillway. The movements of the two gates were simulated using a dynamic mesh controlled by a User Defined Function (UDF). The simulations were run using the prototype dam as the field test to minimize errors due to scale effects. The simulation results are compared with field test observations. Findings: – The transient flow calculations, accurately predict the two gate discharges compared to field data with the predicted ski-jump jet interference flow pattern similar to the observed shapes. The transient simulations indicate that the main reason for the deflected nappe is the larger opening difference between the two gates as the buttress side gate closes. When both gates are running, the two ski-jump jets interfere in the flip bucket and raise the jet nappe to near the buttress to form a secondary flow on this jet nappe surface. As the gate continues to close, the nappe surface continues to rise and the surface secondary flow become stronger, which deflects the nappe over the side buttress. Originality/value: – A dynamic mesh is used to simulate the transient flow behavior of two prototype running gates. The transient flow simulation clarifies the hydraulics mechanism for how the two ski-jump jets interfere and deflect the nappe.